Exposure to Radiofrequency Radiation Emitted from Common Mobile Phone Jammers Alters the Pattern of Muscle Contractions: an Animal Model Study - Rafati, A. (J Biomed Phys Eng, 2015)
INTRODUCTION: The rapid growth of wireless communication technologies has caused public concerns regarding the biological effects of electromagnetic radiations on human health. Some early reports indicated a wide variety of non-thermal effects of electromagnetic radiation on amphibians such as the alterations of the pattern of muscle extractions. This study is aimed at investigating the effects of exposure to radiofrequency (RF) radiation emitted from mobile phone jammers on the pulse height of contractions, the time interval between two subsequent contractions and the latency period of frog’s isolated gastrocnemius muscle after stimulation with single square pulses of 1V (1 Hz). MATERIALS AND METHODS: Frogs were kept in plastic containers in a room. Animals in the jammer group were exposed to radiofrequency (RF) radiation emitted from a common Jammer at a distance of 1m from the jammer’s antenna for 2 hours while the control frogs were only sham exposed. Then animals were sacrificed and isolated gastrocnemius muscles were exposed to on/off jammer radiation for 3 subsequent 10 minute intervals. Isolated gastrocnemius muscles were attached to the force transducer with a string. Using a PowerLab device (26-T), the pattern of muscular contractions was monitored after applying single square pulses of 1V (1 Hz) as stimuli. RESULTS: The findings of this study showed that the pulse height of muscle contractions could not be affected by the exposure to electromagnetic fields. However, the latency period was effectively altered in RF-exposed samples. However, none of the experiments could show an alteration in the time interval between two subsequent contractions after exposure to electromagnetic fields. CONCLUSION: These findings support early reports which indicated a wide variety of non-thermal effects of electromagnetic radiation on amphibians including the effects on the pattern of muscle extractions.